Constructing Meaning through Deictic Expressions in EFL Student’s Poetry: A Pragmatic Analysis - Egi Raputri; Eggi Pratama; Aulia Andhini; Rahma Widi; Annisa Tasyakurna; Hafni Hafsah; Ade Dwi Cahyanti (CV Wahana Publikasi, 2026)
This research investigated the use of deictic expressions in students’ poems. It also explored the interpretation of deictic expressions and identified the most dominant types used in the poems. Deixis plays an important role in language use because the interpretation of deictic expressions depends on contextual information. This research occupied a descriptive qualitative approach. The data were obtained from twelve poems written by students and analyzed using Levinson’s (1983) theory of deixis, which classifies deixis into five categories: person deixis, place deixis, time deixis, discourse deixis, and social deixis. The data analysis involved identifying deictic expressions, classifying them into their respective categories, interpreting their contextual meanings, and calculating the frequency of occurrence of each type. The findings revealed that all five types of deixis were identified in the students’ poems, with a total of 214 deictic expressions found in the data. Person deixis was identified as the most dominant type with 145 occurrences (67.76%), followed by place deixis with 27 occurrences (12.62%), while time deixis and discourse deixis each occurred 20 times (9.35%). Social deixis was identified as the least frequent type with only 2 occurrences (0.93%). The findings indicate that students tended to use poetry as a medium for expressing personal emotions, experiences, and perspectives. Furthermore, this study highlights that deictic expressions play a significant role in constructing contextual meaning and assisting readers in interpreting poetic texts effectively. This research contributes to pragmatic studies in EFL contexts by demonstrating how learners employ deictic resources to develop meaning, establish relationships between textual elements, and enhance their pragmatic competence in creative writing.